2017
DOI: 10.1038/modpathol.2017.11
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological and molecular characterization of SMARCA4-deficient thoracic sarcomas with comparison to potentially related entities

Abstract: Background: Successful multimodality management of advanced soft tissue sarcomas (STS) remains a clinical challenge. Although immune checkpoint blockade has shown great promise, only a minority of patients respond. Improved biomarkers could benefit the treatment choice, since cytotoxic therapies and radiotherapy (RT) can alter the immune milieu. The objective of this study was to characterize PD-L1 expression in locally advanced STS with or without preoperative RT. Design: Tissue microarrays (TMA) were constru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
299
2
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 180 publications
(314 citation statements)
references
References 50 publications
6
299
2
7
Order By: Relevance
“…The cytologic features described here recapitulate the histology of SMARCA4-DTSs [2, 3]. These tumors have been shown to be histologically similar among cases, displaying diffuse sheets of poorly cohesive, relatively monotonous undifferentiated ovoid/epithelioid cells with vesicular chromatin, and prominent nucleoli.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…The cytologic features described here recapitulate the histology of SMARCA4-DTSs [2, 3]. These tumors have been shown to be histologically similar among cases, displaying diffuse sheets of poorly cohesive, relatively monotonous undifferentiated ovoid/epithelioid cells with vesicular chromatin, and prominent nucleoli.…”
Section: Discussionmentioning
confidence: 68%
“…Schaefer et al [6] performed immunohistochemistry for claudin-4 on various tumors and found that the expression of claudin-4 was frequent in carcinomas (including SWI/SNF complex-deficient ones) and epithelial components of synovial sarcomas, whereas almost all the sarcomas investigated were negative for this marker. Indeed, a uniform lack of claudin-4 expression in SMARCA4-DTS was observed in a case series by Yoshida et al [2] as well as in our case, suggesting that SMARCA4-DTSs are true sarcomas and do not represent the least differentiated variants of lung carcinomas.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Loss of SMARCA4 expression through truncating mutations or deep deletions of the SWI/SNF‐related, matrix‐associated, actin‐dependent regulator of chromatin, subfamily A, member 4 ( SMARCA4 ) gene have recently been detected in a subset of UUS . These tumours share overlapping clinicopathological and genetic features with other SMARCA4‐deficient cancers, such as ovarian small cell carcinoma of hypercalcaemic type, atypical teratoid/rhabdoid tumours and thoracic sarcomas . SMARCA4‐deficient UUS are large bulky masses involving the endomyometrium that are composed of sheets of large discohesive and uniformly atypical epithelioid cells with eccentric round to oval nuclei, vesicular chromatin, prominent nucleoli and scant to abundant eosinophilic cytoplasm.…”
Section: Uusmentioning
confidence: 99%